WATER CARRYING CAPACITY BASED ON ECOSYSTEM SERVICES IN URBAN AGRICULTURE OF PALU - Nursalam Nursalam; Nur Edy (AGROLAND The Agricultural Sciences Journal (e-Journal), 2020)
Urban agriculture grows increasingly in tropical countries. It develops not only to feed the growth of the population but also to provide green space, biodiversity, and recreational landscaping. However, developing urban agriculture is facing the problem of water provision. This study examines the existence of agricultural land in Palu, investigates the distribution of agricultural land use in each district, and analyzes the status of environmental carrying capacity for provisioning water. The environmental carrying capacity for provisioning water was assessed based on ecosystem services analysis. The total area of agricultural land in Palu is 5,892.06 ha or about 16.52% of the total area, which spreads in all districts. Three districts recorded have the more extensive agricultural lands, Mantikulore, Tawaeli, and North Palu, of each, has 2188.12 ha (14%), 1090.89 ha (18.51%), and 723.88 ha (12.29%) respectively. The status of water carrying capacity ranged from moderate to high levels, covering an area of ​​5,189.95 ha or 88.08% of the total area of ​​agricultural land. The low carrying capacity of water provision covers ​​689.31 ha or about 11.84% of the total agricultural land. The district of West and South Palu calculated to have the highest carrying capacity. However, both districts experienced a decrease in agricultural land space due to urban development. This study's finding contributes to essential data for relevant authorities in decisions making for sustainable development of urban agriculture in Palu.